2004
DOI: 10.1097/01.tp.0000101009.91516.fc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcome after liver transplantation: utility of the model for end-stage liver disease and a newly derived discrimination function1

Abstract: The MELD score is a relatively poor predictor of posttransplant outcome. In contrast, a model based on four pretransplant variables (recipient age, mechanical ventilation, dialysis, and retransplantation) had a better ability to predict outcome. Our results support the use of MELD for liver allocation and indicate that statistical modeling, such as reported in this article, can be used to identify futile cases in which expected outcome is too poor to justify transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
184
3
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(205 citation statements)
references
References 29 publications
11
184
3
3
Order By: Relevance
“…Another group compared MELD versus Child for the same purpose favoring the first one ( -statistic < 0.7) [9,18]. Some authors stated that a MELD score >25 has AUROC of 0.54 and 0.55 for predicting patient survival following 3 and 12 months of transplantation [19], while other groups behalf similar survival prediction (AUROC of 0.58, 0.67, and <0.61) [20]. Most of these studies did not include a pure cohort of cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group compared MELD versus Child for the same purpose favoring the first one ( -statistic < 0.7) [9,18]. Some authors stated that a MELD score >25 has AUROC of 0.54 and 0.55 for predicting patient survival following 3 and 12 months of transplantation [19], while other groups behalf similar survival prediction (AUROC of 0.58, 0.67, and <0.61) [20]. Most of these studies did not include a pure cohort of cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lower survival rates in patients with higher MELD scores have been assessed before [7,8]. However, the performance of MELD in prediction of post-LT events has been explored with poor results [7][8][9][10][11][12][13][14]. Outcomes after transplantation depend on a number of pre-and post-LT factors, which include both recipient and donor fitness, surgeon's skills, and transplant unit team's experience.…”
Section: Introductionmentioning
confidence: 99%
“…16 To develop a liver graft allocation system that incorporates the principle of utility, the development of a model that predicts posttransplant outcomes is necessary. Since MELD or CTP scores are unable to accurately predict postoperative patient survival, [5][6][7]12 identification of preoperative parameters that correlate with outcomes is mandatory. Indeed, it seems implausible that any system, which needs to combine justice and utility in liver graft allocation, would not include donor or other variables that have been shown to be important.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MELD score was unable to predict early (90-d) postoperative mortality in almost all of the relevant studies. [5][6][7] To increase their accuracy, the most recent models for the prediction of early postoperative mortality have included the MELD score and many other variables, such as serum sodium, 8 donor quality 9 or serum cholinesterase. 10 Prediction of long-term survival alone after liver transplantation is less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…31 Several recipient characteristics can increase the risk of poor DCD outcomes, including high Model for End-stage Liver Disease scores, which have been associated with graft failure and biliary complications in some studies, whereas other studies refute this claim. 26,38,39 In addition, hepatitis C viruspositive recipients may be at increased risk for hepatitis C virus recurrence. 40,41 Recently, Croome and associates found that transplant recipients with hepatocellular carcinoma may have inferior survival rates after DCD transplant (P = .049).…”
mentioning
confidence: 99%